MEASUREMENT OF RENAL SIZE IN RELATION TO BODY HABITUS USING COMPUTED TOMOGRAPHY - MS. LAVANYA B C; MR. SURESH SUKUMAR2 (International Journal of Pharma and Bio Sciences, 2016)
AIM: Measurement of renal size in relation to body habitus using computed tomography OBJECTIVES: To measure the renal sizes. To find the variation between age, gender and body mass index (BMI). METHODOLOGY: By using MDCT kidney length & width were measured on oblique coronal reformatted CT images of 93 patients who all received routine abdominal CT scan with no pathology associated with renal. The patients had normal creatinine levels, no history of renal disease, & normal-appearing on CT. patient weight, height, & gender were recorded. RESULT: The mean of LRT (length of right kidney) in males 94.6±7.45 SD and in females 96.82±7.73 SD. Mean of LLT (length of left kidney) in males 95.42±6.76 and in females 97.56± 6.88SD. Mean WRT (width of right kidney) in males 45.08 ± 5.0 and in females 46.73±4.50 SD and WLT (width of left kidney) in females 47.63 ± 4.95 SD, Keeping P-value of 0.05. There was no statistical significance difference between the renal size with body habitus also with age and gender. CONCLUSION: Normal renal size does not vary according to patient’s body habitus. No relationship was found between renal sizes and age. Renal size is independent of the age and BMI. Similarly the gender also does not affect the renal size. Coronal section of abdominal CT predicts the renal length more accurately than any other imaging techniques, but all imaging techniques were always associated with small prediction errors. Further studies are possible with a larger sample size to find out the variation